Optimal evaluation method for gel system of organic phenolic aldehyde crosslinking agent
By systematically evaluating and analyzing the influencing factors and performance of the organic phenolic crosslinking agent gel system, gel system formulas suitable for different colloid strengths and reservoir characteristics were screened, which solved the problem of lack of systematic evaluation in the prior art and improved the performance of the gel system under high temperature and high mineralization conditions.
Patent Information
- Application Number
- CN202411591320.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art lacks systematically evaluating the applicability of organic phenolic crosslinking agent gel systems, especially under high temperature and high mineralization conditions, its thermal stability and sealing properties are affected.
A preferred evaluation method for the organic phenolic crosslinking agent gel system is proposed. Through systematic experiments to evaluate and analyze the performance and influencing factors of the gel system formula, a gel system formula suitable for different colloid strengths and performances is selected. The specific steps include analyzing the influencing factors of the gel system, evaluating the gel performance, selecting the preferred formula for water blocking rate test, testing the selective blocking ability and dissection adjustment experiment.
Through this method, suitable gel system formulas can be screened for reservoir characteristics, improve their thermal stability and sealing performance under high temperature and high mineralization conditions, and ensure their effective application in oil field development.
Smart Images

Figure CN119510683A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas field development, and particularly relates to a method for optimizing and evaluating an organic phenolic crosslinking agent gel system. Background Art
[0002] Organic phenolic crosslinker gel system plays a variety of roles in oilfield development, mainly including profile control and water plugging, improving oil recovery and improving mobility ratio.
[0003] Organic phenolic gel system can effectively block high permeability layers and reduce water channeling by adjusting the mobility ratio of the reservoir, thereby increasing the swept volume of the injectant. For example, in the Bohai Oilfield, the use of gel plugging agent can effectively improve the mobility ratio and increase the swept volume of the injectant.
[0004] The organic phenolic gel system achieves the purpose of controlling water and increasing oil production through the dual effects of deep profile adjustment (or fluid diversion) and oil displacement. For example, weak cross-linked gel displacement technology is one of the effective methods to improve the recovery rate of water-flooded reservoirs. Its mechanism is to achieve the purpose of controlling water and increasing oil production through the dual effects of deep profile adjustment and oil displacement.
[0005] High temperature and high mineralization conditions will affect the thermal stability and plugging performance of the organic phenolic gel system.
[0006] Currently, there is no method for optimizing and evaluating the organic phenolic crosslinker gel system to systematically evaluate the applicability of the organic phenolic crosslinker gel system. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a method for optimizing and evaluating an organic phenolic crosslinker gel system, which can screen out gel system formulas with different colloid strengths and good performance according to reservoir characteristics by systematically experimentally evaluating and analyzing the performance and influencing factors of the gel system formula.
[0008] The technical solution of the present invention is: a method for optimizing and evaluating an organic phenolic crosslinking agent gel system, which is special in that it comprises the following steps:
[0009] S1. Factors affecting the analysis of gel system
[0010] S1.1. Test the effect of polymer concentration on the gel system;
[0011] S1.2. Test the effect of cross-linker concentration on the gel system;
[0012] S1.3, test the effect of cross-linking aid on gel system;
[0013] S1.4. Effect of test temperature on gel system;
[0014] S1.5. Test the effect of mineralization on the gel system;
[0015] S2. Evaluate the performance of the gel system:
[0016] S2.1. Test the effect of mechanical shear on the gel system;
[0017] S2.2. Test the effect of porous medium shear on the gel system;
[0018] S2.3, test the stability of the gel system;
[0019] S2.4. Select the above preferred organic phenolic crosslinker gel formula to conduct water plugging rate test;
[0020] S2.5, testing the selective plugging ability of the above preferred organic phenolic crosslinker gel formula;
[0021] S2.6. Conduct profile control experiments on the above preferred organic phenolic crosslinker gel formula and calculate the recovery factor.
[0022] Furthermore, in step S1.1, the effect of the test polymer concentration on the gel system is specifically as follows:
[0023] The organic phenolic crosslinker gel to be tested is divided into several portions, each with a different polymer concentration, and the gelation time and gelation strength are tested.
[0024] Furthermore, in step S1.2, the effect of the concentration of the test cross-linking agent on the gel system is specifically as follows:
[0025] The organic phenolic crosslinker gel to be tested is divided into several portions, each with a different crosslinker concentration, and the gelation time and gelation strength are tested.
[0026] Furthermore, in step S1.3, the effect of the cross-linking aid on the gel system is tested as follows:
[0027] The organic phenolic crosslinking agent gel to be tested is divided into several portions, and then divided into several groups. Each group is used to test a crosslinking agent concentration. The concentration of the crosslinking agent to be tested in each portion of the same group is different, and the concentrations of other crosslinking agents are the same. The gelation time and gelation strength are tested.
[0028] Furthermore, in step S1.4, the effect of the test temperature on the gel system is specifically as follows:
[0029] The organic phenolic crosslinker gel to be tested is divided into several portions, each portion is placed at a different temperature, and the gelation time and gelation strength are tested.
[0030] Furthermore, in step S1.5, the effect of testing the mineralization on the gel system is specifically as follows:
[0031] The organic phenolic crosslinker gel to be tested is divided into several portions, each portion is placed in liquids with different mineralization degrees, and the gelation time and gelation strength are tested.
[0032] Furthermore, in step S2.1, the effect of mechanical shearing on the gel system is tested as follows:
[0033] The organic phenolic crosslinker gel to be tested is divided into several portions, each with a different polymer concentration. Each portion is sheared for different lengths of time to test the gelation time and gelation strength.
[0034] Furthermore, in step S2.2, the effect of porous medium shear on the gel system is tested as follows:
[0035] The organic phenolic crosslinker gel to be tested is divided into several portions, each with a different polymer concentration, and the gelation time and gelation strength of the porous medium shear sample and the unsheared sample are tested.
[0036] Furthermore, in step S2.3, the stability of the gel system is tested as follows:
[0037] The organic phenolic crosslinking agent gel to be tested is divided into several portions, each portion has a different polymer concentration, and each portion is placed for several days for aging to observe the dehydration condition.
[0038] Furthermore, in step S2.4, the water plugging rate test is carried out by selecting the above preferred organic phenolic crosslinking agent gel formula as follows:
[0039] The organic phenolic crosslinker gel to be tested is divided into several portions, each with a different injection volume. The permeability before injection and the permeability after injection are tested, and the plugging rate is calculated.
[0040] Furthermore, in step S2.5, the selective plugging ability of the above preferred organic phenolic crosslinker gel formula is tested as follows:
[0041] Two groups of core combinations with different permeabilities were taken, and the water flow rate during water flooding and the water volume after polymer gel injection were tested successively. The change in water flow rate before and after gel injection was calculated, and finally the profile improvement rate was obtained.
[0042] Furthermore, in step S2.6, a profile control experiment is conducted on the above preferred organic phenolic crosslinker gel formula, and the recovery factor is calculated as follows:
[0043] Profile control experiments were conducted by injecting an organic phenolic crosslinker gel formulation into an interlayer heterogeneous reservoir model to calculate enhanced oil recovery;
[0044] The profile control experiment was conducted by injecting an organic phenolic crosslinker gel formula into an intra-layer heterogeneous reservoir model and calculating the enhanced oil recovery.
[0045] The beneficial effect of the present invention is that the preferred evaluation method for the organic phenolic crosslinker gel system proposed in the present invention can screen out gel system formulas with different colloid strengths and good performance according to reservoir characteristics by systematically experimentally evaluating and analyzing the performance and influencing factors of the gel system formula. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 is the effect of polymer concentration on gel properties;
[0047] Figure 2 is the effect of cross-linker concentration on gel properties;
[0048] Figure 3 is the effect of the concentration of the cross-linking aid JB on the gel properties;
[0049] Figure 4 is the effect of the concentration of cross-linking aid B on the gel properties;
[0050] Figure 5 is the effect of the concentration of the cross-linking aid JQ on the gel properties;
[0051] Figure 6 is the effect of the concentration of cross-linking aid L on the gel properties;
[0052] Figure 7 is the effect of temperature on gel strength;
[0053] Figure 8 It is the effect of temperature on gel formation time;
[0054] Fig. 9 is the effect of mineralization on gel properties;
[0055] Fig.10 is the effect of mechanical shear on gel properties;
[0056] Fig.11 is the effect of mechanical shear on gel properties;
[0057] Fig.12 is the effect of mechanical shear on gel properties;
[0058] Fig.13 is the effect of porous medium shear on gel properties;
[0059] Fig.14 It is a gel stability evaluation test;
[0060] Fig.15 It is a plan view of the flat plate sand filling model. DETAILED DESCRIPTION
[0061] An organic phenolic crosslinking agent gel system was developed according to the method and steps for developing a chromium ion crosslinking agent gel system. The basic formula obtained from the research is as follows:
[0062] Table 1 Basic formula of organic phenolic crosslinker gel system
[0063]
[0064] The following will evaluate whether the organic phenol-formaldehyde crosslinking agent gel system is suitable for the oil reservoir of the Changqing Oilfield Production Plant No. 4 according to the preferred evaluation method of the organic phenol-formaldehyde crosslinking agent gel system proposed by the present invention.
[0065] S1. Factors affecting the analysis of gel system
[0066] S1.1. Test the effect of polymer concentration on the gel system: Divide the organic phenolic crosslinker gel to be tested into several portions, each with a different polymer concentration, and test the gelation time and gelation strength.
[0067] The effect of polymer concentration on the gel system is shown in Table 2 and Figure 1 The higher the polymer concentration, the shorter the gelation time and the higher the viscosity.
[0068] The AP-P4 concentration is 500 mg / L, the viscosity is 8 mPa.s, and it does not form gel; the AP-P4 concentration is 1000 mg / L, the system viscosity is 4200 mPa.s; the AP-P4 concentration is 1500 mg / L, the system viscosity is 9400 mPa.s; the AP-P4 concentration is 3000 mg / L, the system viscosity is 51800 mPa.s.
[0069] Table 2 Effect of polymer concentration on gel system performance
[0070]
[0071] S1.2. Test the effect of cross-linking agent concentration on the gel system: divide the organic phenolic cross-linking agent gel to be tested into several portions, each with a different cross-linking agent concentration, and test the gelation time and gelation strength.
[0072] The effect of the concentration of crosslinker W on the gel system is shown in Table 3.
[0073] Table 3 Effect of crosslinker W concentration on gel system
[0074]
[0075]
[0076] From Table 3 and Figure 2It can be seen that the higher the cross-linking agent concentration, the faster the gel system gels and the greater the colloid strength. When the polymer concentration is 1000 mg / L, the appropriate concentration of W is 200 mg / L; when the polymer concentration is 2000 mg / L, the appropriate concentration of W is 300 mg / L.
[0077] S1.3. Test the effect of cross-linking agents on the gel system: Divide the organic phenolic cross-linking agent gel to be tested into several portions, and then divide them into several groups. Each group is used to test a cross-linking agent concentration. The concentration of the cross-linking agent to be tested in each portion of the same group is different, and the concentrations of other cross-linking agents are the same. Test the gelation time and gelation strength.
[0078] The effect of crosslinking aid JB on the gel system is shown in Table 4.
[0079] Table 4 Effect of cross-linking agent JB concentration on gel system
[0080]
[0081] As shown in Table 4, JB has little effect on the strength of the system; it has a great effect on the gelation time of the system, has a good accelerating effect, and can adjust the gelation time; it has a great effect on the stability of the system, and the system without JB begins to dehydrate after 15 days. The polymer concentration is 1000mg / L~2000mg / L, and the appropriate concentration of JB is 75mg / L~100mg / L.
[0082] The effect of crosslinking aid B on the gel system is shown in Table 5.
[0083] Table 5 Effect of crosslinking agent B concentration on gel system
[0084]
[0085] From Table 5 and Figure 4 It can be seen that B has little effect on the crosslinking time, has a certain effect on the gel strength, and has a greater effect on the stability. With the increase of B concentration, the colloid strength of the system rises rapidly, but after the concentration exceeds a certain value, the increase in gel strength slows down. The system without B began to dehydrate after 20 days, while the system with B did not dehydrate within 5 months. The polymer concentration is 1000mg / L~2000mg / L, and the concentration of B is 200mg / L~300mg / L.
[0086] The effect of cross-linking agent JQ on the gel system is shown in Table 6.
[0087] Table 6 Effect of cross-linking agent JQ concentration on gel system
[0088]
[0089] From Table 6, Figure 5It can be seen that with the increase of JQ concentration, the gel strength increases rapidly and the gel time shortens accordingly, but if the concentration exceeds a certain value, the colloid dehydrates, the viscosity decreases, and the stability deteriorates. The polymer concentration is 1000mg / L~2000mg / L, and the JQ concentration is 1000mg / L~1200mg / L~1500mg / L.
[0090] The effect of crosslinking aid L on the gel system is shown in Table 7.
[0091] Table 7 Effect of cross-linking agent L concentration on gel system
[0092]
[0093] From Table 7 and Figure 6 It can be seen that the crosslinking agent L has a good effect on the gel system, which has the effects of extending the gelation time, increasing the colloid strength and stabilizing the system. The system without L began to dehydrate after 15 days, and the system with 150mg / L to 200mg / L did not dehydrate within 5 months. The colloid was transparent and uniform, and the system was very stable.
[0094] S1.4. Test the effect of temperature on the gel system: Divide the organic phenolic crosslinker gel to be tested into several portions, place each portion at a different temperature, and test the gelation time and gelation strength.
[0095] The effect of temperature on the gel system is shown in Table 8.
[0096] Table 8 Effect of temperature on gel system performance
[0097]
[0098] As can be seen from Table 8, temperature has a great influence on the gelation time of the system. The higher the temperature, the shorter the gelation time. The gelation time of the system is shortened by more than half from 40℃ to 60℃. Temperature also has a great influence on the stability of the system. The higher the temperature, the worse the stability of the gel system. Temperature has a great influence on the gelation strength of the system. The higher the temperature, the lower the gelation strength of the system. When the temperature reaches 80℃, the strength of the system with a polymer concentration of 1000mg / L is reduced to 3970mPa.s, while the strength of the system at 70℃ is 4320mPa.s. Temperature has a great influence on the stability of the system. The higher the temperature, the worse the stability of the gel system. At 80℃, the gel began to have an uneven colloid tendency after 4 months, and flocculent substances appeared in the colloid; at 60℃, the gel did not dehydrate after 5 months; the system with a temperature below 60℃ did not dehydrate, and the colloid was better.
[0099] S1.5. Test the effect of mineralization on the gel system: Divide the organic phenolic crosslinker gel to be tested into several portions, place each portion in liquids with different mineralizations, and test the gelation time and gelation strength.
[0100] The effect of mineralization on the gel system is shown in Table 9.
[0101] Table 9 Effect of mineralization on gel system performance
[0102]
[0103] It can be seen from Table 9 that the mineralization degree has little effect on the gelation time of the system.
[0104] From Table 9 and Fig. 9 It can be seen that the mineralization has a great influence on the performance of the gel. The gel strength of the gel system decreases with the increase of mineralization, and the decrease is relatively large.
[0105] S2. Evaluate the performance of the gel system:
[0106] S2.1. Test the effect of mechanical shearing on the gel system: Divide the organic phenolic crosslinker gel to be tested into several portions, each with a different polymer concentration. Shear each portion for different lengths of time to test the gelation time and gelation strength.
[0107] The effect of mechanical shear on the gel system is shown in Table 10.
[0108] Table 10 Effect of mechanical shear on gel system performance
[0109]
[0110] From Table 10 and Figures 10-12 It can be seen that polymer concentrations of 1000mg / L, 2000mg / L and 3000mg / L can all gel after mechanical shearing, but the gel time is relatively extended. The longer the shear time, the longer the gel time. The gel strength has a certain decrease after mechanical shearing. The longer the shear time, the more the gel strength decreases, but the decrease is not very large, indicating that the gel system has good shear resistance.
[0111] S2.2. Test the effect of porous medium shear on the gel system: Divide the organic phenolic crosslinker gel to be tested into several portions, each with a different polymer concentration, and test the gelation time and gelation strength of the porous medium sheared sample and the unsheared sample. The effect of porous medium shear on the gel system is shown in Table 11.
[0112] Table 11 Effect of porous medium shear on gel system performance
[0113]
[0114] From Table 11 and Fig.13 It can be seen that the gel after shearing has a longer gelation time, a lower colloid strength and a better stability than the gel without shearing.
[0115] S2.3. Test the stability of the gel system: divide the organic phenolic crosslinker gel to be tested into several portions, each with a different polymer concentration, and place them for several days for aging to observe the dehydration.
[0116] The stability test results are shown in Table 13.
[0117] Table 12 Effect of polymer concentration on gel system performance
[0118]
[0119] Table 13 Gel stability evaluation results
[0120]
[0121] From Table 13 and Fig.14 It can be seen that after 5 months of aging, the gel system did not dehydrate, and the gel system formulas all had good stability.
[0122] S2.4. Select the preferred organic phenolic crosslinker gel formula above to carry out water plugging rate test: divide the organic phenolic crosslinker gel to be tested into several portions, inject different amounts of each portion, test the permeability before injection and the permeability after injection, and calculate the plugging rate.
[0123] The experimental results of water plugging rate of the formula 1000AP+200W+50JB+200B+1000JQ+150L are shown in Table 14.
[0124] Table 14 Effect of gel injection volume on plugging rate
[0125]
[0126]
[0127] It can be seen that the blocking rate can reach 99.61%.
[0128] S2.5. Test the selective plugging ability of the above preferred organic phenolic crosslinker gel formula: Take two groups of core combinations with different permeabilities, test the water flow rate during water flooding and the water volume after polymer gel injection, calculate the change in water flow rate before and after gel injection, and finally obtain the profile improvement rate.
[0129] The experimental results of the selective plugging ability of the formula 1000AP+200W+50JB+200B+1000JQ+150L are shown in Table 15.
[0130] It can be seen that the greater the difference between the high and low permeability layers, the more obvious the profile improvement effect. When the difference is 4.6, the profile improvement rate is 91.77%.
[0131] Table 15 Core test results of profile change of profile control system
[0132]
[0133] S2.6. Perform profile control experiments on the above preferred organic phenolic crosslinker gel formula and calculate the recovery rate:
[0134] Profile control experiments were conducted by injecting an organic phenolic crosslinker gel formulation into an interlayer heterogeneous reservoir model to calculate enhanced oil recovery;
[0135] The relevant experimental results of the profile control system of 1000AP+200W+50JB+200B+1000JQ+150L are as follows:
[0136] Table 16 Basic parameters of sand filling
[0137]
[0138]
[0139] Table 17 Experimental process and results
[0140] Injection order Number of pv injected Flow rate (ml / h) Injection pressure (MPa) Profile improvement rate (%) Water flooding 2.0 60 0.086 / gel 0.4 30 2.3 96.51 Subsequent water flooding 2.0 10 5.7 /
[0141] Table 18 Gel profile control to improve oil recovery experimental results
[0142]
[0143] It can be seen from Tables 17 and 18 that the profile improvement rate can reach 96.51%, the subsequent water drive pressure is increased from 0.086MPa to 5.7MPa, and the recovery factor of the laboratory indoor physical model is increased by more than 4.63 percentage points.
[0144] The profile control experiment was conducted by injecting an organic phenolic crosslinker gel formula into the in-layer heterogeneous reservoir model, and the enhanced oil recovery was calculated:
[0145] The experimental results of improving the residual resistance coefficient by the profile control formula of 1000AP+200W+50JB+200B+1000JQ+150L are shown in Table 19. As can be seen from Table 19, the water injection pressure is significantly increased after profile control, and the residual resistance coefficient is relatively high.
[0146] Table 19 Flow characteristics of profile control system in core
[0147]
[0148] Using the plane sand filling model Fig.15Simulate the recovery rate improvement. The size of the plane sand filling model is: 200mm×200mm×6mm, and the effective pore volume is about: 100cm 3 . Fill with quartz sand of 40-120 mesh. Plane uneven sand filling: On the diagonal line, quartz sand of 20-40 mesh is used for filling to form a high permeability zone with a width of 10-20mm. During the sand filling process, the proportion of coarse sand particles on the diagonal line is changed in the order of the four corner wells to form a certain plane heterogeneity.
[0149] The central well was saturated with water and oil respectively, and then injected into a corner well, and the wells on the opposite corner produced, and water drove the oil. When the water content reached 90%, 0.4PV of gel system was injected, and the gel was allowed to solidify for 72 hours, followed by 10PV of water drive. The basic parameters of the heterogeneous model are shown in Table 20, and the experimental results are shown in Table 21.
[0150] Table 20 Basic data of flat plate model
[0151] parameter Original oil saturation Immune water saturation Recovery rate Residual oil saturation Flat panel model 72.3% 27.7% 36.7% 63.3%
[0152] Table 21 Profile adjustment and enhanced oil recovery results
[0153] parameter gel Subsequent water flooding Improved oil recovery Ultimate recovery Improved oil recovery % 8.82 7.06 15.88 52.58
[0154] According to Table 21, after profile adjustment, the recovery factor of the laboratory indoor physical model increased by 15.88%.
[0155] In summary, in view of the characteristics of the oil reservoir of the Fourth Oil Production Plant of Changqing Oilfield, the method proposed in the present invention was used to conduct a systematic experimental evaluation and analysis on the performance and influencing factors of the developed organic phenolic cross-linked gel system, and a series of gel system formulas with different colloid strengths and good performance were screened out. Mechanical shear and porous medium shear experiments show that the strength of the gel is reduced and the gelation time is prolonged, which is conducive to large-dose injection, improves its stability, ensures that the gel is gelled at the target location, and plays a role in profile adjustment. The organic phenolic cross-linked gel system can adapt to the characteristics of the oil reservoir of the Fourth Oil Production Plant of Changqing Oilfield, and has heat resistance, salt resistance, and shear resistance; good injectability; and good stability.
Claims
1. A method for optimizing and evaluating an organic phenolic crosslinker gel system, characterized in that: The following steps are involved: S1. Factors affecting the analysis of gel system S1.
1. Test the effect of polymer concentration on the gel system; S1.
2. Test the effect of cross-linker concentration on the gel system; S1.3, test the effect of cross-linking aid on gel system; S1.
4. Effect of test temperature on gel system; S1.
5. Test the effect of mineralization on the gel system; S2. Evaluate the performance of the gel system: S2.
1. Test the effect of mechanical shear on the gel system; S2.
2. Test the effect of porous medium shear on the gel system; S2.3, test the stability of the gel system; S2.
4. Select the above preferred organic phenolic crosslinker gel formula to conduct water plugging rate test; S2.5, testing the selective plugging ability of the above preferred organic phenolic crosslinker gel formula; S2.
6. Conduct profile control experiments on the above preferred organic phenolic crosslinker gel formula and calculate the recovery factor.
2. The method for optimizing and evaluating the organic phenolic crosslinker gel system according to claim 1, characterized in that: In step S1.1, the effect of the test polymer concentration on the gel system is specifically as follows: The organic phenolic crosslinker gel to be tested is divided into several portions, each with a different polymer concentration, and the gelation time and gelation strength are tested.
3. The method for optimizing and evaluating the organic phenolic crosslinker gel system according to claim 2, characterized in that: In step S1.2, the effect of the concentration of the test cross-linking agent on the gel system is specifically as follows: The organic phenolic crosslinker gel to be tested is divided into several portions, each with a different crosslinker concentration, and the gelation time and gelation strength are tested.
4. The method for optimizing and evaluating the organic phenolic crosslinker gel system according to claim 3, characterized in that: In step S1.3, the effect of the cross-linking aid on the gel system is tested as follows: The organic phenolic crosslinking agent gel to be tested is divided into several portions, and then divided into several groups. Each group is used to test a crosslinking agent concentration. The concentration of the crosslinking agent to be tested in each portion of the same group is different, and the concentrations of other crosslinking agents are the same. The gelation time and gelation strength are tested.
5. The method for optimizing and evaluating the organic phenolic crosslinker gel system according to claim 4, characterized in that: In step S1.4, the effect of the test temperature on the gel system is specifically as follows: The organic phenolic crosslinking agent gel to be tested is divided into several portions, each portion is placed at different temperatures, and the gelation time and gelation strength are tested; In step S1.5, the effect of testing the mineralization on the gel system is specifically as follows: The organic phenolic crosslinker gel to be tested is divided into several portions, each portion is placed in liquids with different mineralization degrees, and the gelation time and gelation strength are tested.
6. The method for optimizing and evaluating the organic phenolic crosslinker gel system according to claim 5, characterized in that: In step S2.2, the effect of porous medium shear on the gel system is tested as follows: The organic phenolic crosslinker gel to be tested is divided into several portions, each with a different polymer concentration, and the gelation time and gelation strength of the porous medium shear sample and the unsheared sample are tested.
7. The method for optimizing and evaluating the organic phenolic crosslinker gel system according to claim 6, characterized in that: In step S2.3, the stability of the gel system is tested as follows: The organic phenolic crosslinking agent gel to be tested is divided into several portions, each portion has a different polymer concentration, and each portion is placed for several days for aging to observe the dehydration condition.
8. The method for optimizing and evaluating the organic phenolic crosslinker gel system according to claim 7, characterized in that: In step S2.4, the water plugging rate test is carried out by selecting the above preferred organic phenolic crosslinking agent gel formula as follows: The organic phenolic crosslinker gel to be tested is divided into several portions, each with a different injection volume. The permeability before injection and the permeability after injection are tested, and the plugging rate is calculated.
9. The method for optimizing and evaluating the organic phenolic crosslinker gel system according to claim 8, characterized in that: In step S2.5, the selective plugging ability of the above preferred organic phenolic crosslinker gel formula is tested as follows: Two groups of core combinations with different permeabilities were taken, and the water flow rate during water flooding and the water volume after polymer gel injection were tested successively. The change in water flow rate before and after gel injection was calculated, and finally the profile improvement rate was obtained.
10. The method for optimizing and evaluating the organic phenolic crosslinking agent gel system according to claim 9, characterized in that: In step S2.6, a profile control experiment is conducted on the preferred organic phenolic crosslinker gel formula, and the recovery factor is calculated as follows: Profile control experiments were conducted by injecting an organic phenolic crosslinker gel formulation into an interlayer heterogeneous reservoir model to calculate enhanced oil recovery; The profile control experiment was conducted by injecting an organic phenolic crosslinker gel formula into an intra-layer heterogeneous reservoir model and calculating the enhanced oil recovery.